Does Type of Residential Housing Matter for Depressive Symptoms in the Aftermath of a Disaster? Insights From the Great East Japan Earthquake and Tsunami. Issue 3 (13th July 2017) - Sasaki, Yuri; Aida, Jun; Tsuji, Taishi; Miyaguni, Yasuhiro; Tani, Yukako; Koyama, Shihoko; Matsuyama, Yusuke; Sato, Yukihiro; Tsuboya, Toru; Nagamine, Yuiko; Kameda, Yoshihito; Saito, Tami; et al.
Abstract: The 2011 Great East Japan Earthquake and Tsunami resulted in widespread property destruction and over 250, 000 displaced residents. We sought to examine whether the type of housing arrangement available to the affected victims was associated with a differential incidence of depressive symptoms. In this prospective cohort study, which comprised participants aged ≥65 years from Iwanuma as a part of the Japan Gerontological Evaluation Study, we had information about the residents' mental health both before the disaster in 2010 and 2.5 years afterward. The Geriatric Depression Scale was used. Type of accommodation after the disaster was divided into 5 categories: no move, prefabricated housing (temporary housing), existing private accommodations (temporary apartment), newly established housing, and other. Poisson regression analysis was adopted, with and without multiple imputation. Among the 2, 242 participants, 16.2% reported depressive symptoms at follow-up. The adjusted rate ratio for depressive symptoms among persons moving into prefabricated housing, compared with those who did not, was 2.07 (95% confidence interval: 1.45, 2.94). Moving into existing private accommodations or other types of accommodations was not associated with depression. The relationship between living environment and long-term mental health should be considered for disaster recovery planning.